STANDARDISATION OF PLOTTING COURSES AND SELECTING TURN POINTS IN MARITIME NAVIGATION - Lušić, Zvonimir; Kos, Serđo; Galić, Stipe (Promet - Traffic&Transportation, 2014)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–>Today’s methods of plotting courses and selecting sailing routes and turn points in maritime navigation are still largely based on subjective assessment of the master or the officer in charge. This results in a great variety of course distribution and, accordingly, in various ship movements. Modern electronic aids, in particular ECDIS (Electronic Chart Display and Information System) can significantly facilitate maritime voyage planning, course plotting, selection of turning points, etc. In addition to displaying electronic charts, the specific feature of these systems is that they facilitate route planning, supervision of ship movements, data recording, database search, alarm setting, etc. However, these systems do not yet provide automatic selection of courses on user’s request in a standardised form. Therefore, in most cases, the routes and turn points are selected empirically or because they have been previously defined and used. This paper shows the drawbacks of the existing methods of selecting routes and plotting courses in maritime navigation and gives recommendations how to improve them.<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:’Table Normal’; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:’’; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:’Times New Roman’; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400; –> <!–[endif] –>